“Vai pono sintido” os saberes das lavadeiras da Cidade de Goiás no saber fazer sabão de bola - Moreira, Gleidson de Oliveira (2022)
This doctorate dissertation, whose title is Vai pono sintido – os saberes das lavadeiras da Cidade de Goiás no saber fazer sabão de bola (Make sense of this – the lore of the laundresses of the Town of Goiás resulting from their expertise in making soap balls) aims to understand the meanings of that artifact, how it has been manufactured, its components, its makers and the techniques involved in its making; I have explored the ways of manufacturing and using the soap ball by considering the memories of the laundresses of the Town of Goiás (Goiás, Brazil). The methodological procedures that have been employed are: a literature exploration, a primary documents list, interviews, field work (in the Town of Goiás), the ethnography of the material culture, an analysis of the technical processes, of photographic records, video productions and drawings. The research question is this: How is soap ball, an artifact of the material culture, able to convey meaning to the life of women who have been ostracized by a “colonizing” society? The paper hypothesis starts from the resurgence of soap ball, which belongs to a network of knowledge of the peasant life from Goiás, as it is an activity that envelopes many forms of permanence and resistance of the rural world in the urban environment of the Town of Goiás. That soap ball ethnography has aimed to follow, by considering the materials (recipes, ingredients, buckets, wooden rods, lye, caustic soda, pans, knives and spoons), the flow of “things and objects” involved in the technical procedures of the manufacture chain and modulated by rhythms, gestures and movements studied by the Anthropology of Techniques. From my maternal grandmother’s reports on her active participation in that process, I have tried to comprehend those ancient forms of knowledge, whose ancestry lies in the fazedeiras (female makers) of soap balls from the Town of Goiás since colonial days. The text has been arranged in four chapters: the first one, “Ethnography of the things biographed by my grandmother”, displays the stories derived from the objects that constitute the places occupied by the laundresses; in the second one, “Being a poor woman in the Town of Goiás”, there is an interpretation of the biased conceptions based on sex discrimination and ethnocentrism towards the professional laundresses in different periods of history; the third one, “The soap ball and its technique: recipes, ingredients and ways to make it”, regards technique as manufacture; lastly, the fourth chapter, “Notebook of Images”, is a section in which I have used pictures as a way to enlarge the written text by articulating speech, written words and images. I hope this work may contribute to the Academy through its reflections concerning the anthropology of the body and the anthropology of technique.